2019
DOI: 10.1038/s41598-019-38626-3
|View full text |Cite|
|
Sign up to set email alerts
|

Holocene El Niño–Southern Oscillation variability reflected in subtropical Australian precipitation

Abstract: The La Niña and El Niño phases of the El Niño-Southern Oscillation (ENSO) have major impacts on regional rainfall patterns around the globe, with substantial environmental, societal and economic implications. Long-term perspectives on ENSO behaviour, under changing background conditions, are essential to anticipating how ENSO phases may respond under future climate scenarios. Here, we derive a 7700-year, quantitative precipitation record using carbon isotope ratios from a single species of leaf preserved in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
94
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 64 publications
4
94
1
1
Order By: Relevance
“…In the tropical Andes (5-13 • S) and the Altiplano (13-22 • S) regions of South America, a set of well-grounded paleoclimate reconstructions have revealed that significant precipitation changes occurred during the most recent millennia (Seltzer et al, 2000;Baker et al, 2005;Giralt et al, 2008;Bird et al, 2011a;Novello et al, 2016), reflecting decadal, centennial, and millennial changes in the mean strength of the South American summer monsoon (SASM). In addition, a composite tree ring chronology from the Altiplano showed that decadal anomalies in SASM-derived precipitation have been strongly modulated by the variability of the El Niño-Southern Oscillation (ENSO) over the last 700 years (Morales et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the tropical Andes (5-13 • S) and the Altiplano (13-22 • S) regions of South America, a set of well-grounded paleoclimate reconstructions have revealed that significant precipitation changes occurred during the most recent millennia (Seltzer et al, 2000;Baker et al, 2005;Giralt et al, 2008;Bird et al, 2011a;Novello et al, 2016), reflecting decadal, centennial, and millennial changes in the mean strength of the South American summer monsoon (SASM). In addition, a composite tree ring chronology from the Altiplano showed that decadal anomalies in SASM-derived precipitation have been strongly modulated by the variability of the El Niño-Southern Oscillation (ENSO) over the last 700 years (Morales et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although barrier island hydrological systems are reasonable climate indicators, due to substantial variability in their short-and long-term climate patterns, the current understanding of these systems is generally poor, especially with respect to groundwater (Schneider and Kruse, 2003;Barr et al, 2013Barr et al, , 2019. In particular, due to recharge rates and residence times of water not being sufficiently investigated, the extent of connectivity between regional groundwater and perched aquifer systems is commonly not well understood.…”
mentioning
confidence: 99%
“…The island is an important part of the coastal environment in south-east Queensland and provides a vital groundwater resource, recreational space for large urban areas and, most importantly, unique coastal ecosystems with many freshwater wetlands, lakes and marine coastal environments . The island also plays a major role in the palaeoclimate reconstructions for the east coast of Australia, as some of the longest sediment records have been extracted from the North Stradbroke Island wetlands (Barr et al, 2013(Barr et al, , 2019Tibby et al, 2016Tibby et al, , 2017. Apart from a small number of government reports (Leach, 2011), there are few studies on the groundwater resources of the island, and, to the best of our knowledge, there is no prior work on MRTs on large Early Quaternary subtropical islands.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The island is an important part of the coastal environment in South East Queensland and provides a vital groundwater resource, recreational space for the large urban areas and most importantly unique coastal ecosystems with many freshwater wetlands, lakes and marine coastal environments (Marshall et al, 2011). The island also plays a major role in the paleoclimate reconstructions for the east coast of Australia as some of the longest sediment records have been extracted from North Stradbroke Island wetlands (Barr et al, 2013;Tibby et al, 2016Tibby et al, , 2017Barr et al, 2019). Apart from a small number of government reports (Leach, 2011), there are few studies of the groundwater resource of the island and there is no prior work on residence times.…”
mentioning
confidence: 99%